Sweden: multiculturalism and specifics of religious freedom’s realization in secular state - N. I. Shumakova (Правоприменение)
Sweden has a long history of being a monoconfessional state. However, in the 20th – 21st centuries the composition of Swedish society has changed, leading the country into a crisis caused by the policy of ignoring the needs of ethnic and religious minorities. In recent years, multidisciplinary research works have been focused on finding a ground of the current social and political destabilization in this country caused by on-going religion- and ethic-based conflicts between its nationals. Some of them suggest that Sweden is not a secular but a clerical state, others – that there is a gap in its legislation.The author of the article offers another point of view, according to which, the Swedish law enforcer distorts the constitutional and legal meaning of the provisions on religious freedom that occurs under the influence of historical specifics of the development of Swedish law, hence the lack of uniformity in law enforcement practice for the implementation of this fundamental human right.The subject of the study is the norms of the legislation of Sweden, including historical legal acts and documents, as well as relevant court cases and key findings of domestic and foreign research works.Objective: to prove the influence of historical specifics of the development of Swedish law on the current legal enforcement practice under which the distortion of the constitutional and legal meaning by the Swedish law enforcement takes place.Methods: the author employs a combination of general (content-analysis, case-study, formal logical method, generalization etc.) and private scientific methods (formal judicial methods, concrete sociological method of studying state and legal phenomena etc).Results: The obtained results demonstrate that Swedish law enforcement has been given an opportunity for a broad interpretation of constitutional norms. The author identifies the distortion of the constitutional and legal meaning in provisions that provide a special status to followers of the evangelical faith, on the one hand, and a partial ban on religious and ethnic minorities from expressing their confessional affiliation, on the other. The analysis of specifics of the development of Swedish law demonstrates the possible ground of the existing constitutional inequality is the historically discriminatory nature of the legislation in relation to followers of other religious cults. These results can be used as a foundation for future research in the field of realization of religious liberty in multicultural states.